The effect of an English TV series with a bimodal subtitle on students' vocabulary acquisition - Miga Yulia; Muhammad Fazaki (English Education Journal, 2022)
Students of English struggle to remember large amounts of new vocabulary, which leads to a lack of vocabulary, and effective teaching methods and media affect students' knowledge of vocabulary. The current research focuses on using bimodal English-subtitled movie series to improve student vocabulary. The purpose of this research was to determine whether the vocabulary of students improved as a result of watching a seven-part English television series with English subtitle. This study employed quantitative approach, and thirty undergraduate students majoring in EFL were chosen to take part in this study. Prior to the intervention, the students were given a test of the vocabulary that was often found in the series, and they were given the same test following the intervention. The data were analyzed using paired sample t-test and the significance level of 0.05 was used to reject the null hypothesis. The finding shows that watching an English TV series with English subtitle significantly enhanced the students’ vocabulary. As a result, it is recommended that learners use an English TV series with English subtitles to improve their English vocabulary.